2012
DOI: 10.1111/j.1532-5415.2011.03838.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intervention Using a Community‐Based Walking Program for Prevention of Mental Decline: A Randomized Controlled Trial

Abstract: Walking programs may provide benefits in some aspects of cognition, QOL, and functional capacity including social interaction in elderly community members. This study could serve as the basis for implementation of a community-based intervention to prevent mental decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 28 publications
4
112
0
1
Order By: Relevance
“…There is evidence that HQOL scores were improved by the intervention of walking and exercising in community settings, and that scores of frontal-lobe functions then increased (Maki et al, 2012). Neuropsychological studies of patients with frontal lesions have reported that impaired executive functions due to frontal-lobe damage are associated with decreasing mental HQOL scores (Chahal, Barker-Collo, & Feigin, 2011;Laffond et al, 2012).…”
Section: Health-related Qol and Cognitive Functionsmentioning
confidence: 99%
“…There is evidence that HQOL scores were improved by the intervention of walking and exercising in community settings, and that scores of frontal-lobe functions then increased (Maki et al, 2012). Neuropsychological studies of patients with frontal lesions have reported that impaired executive functions due to frontal-lobe damage are associated with decreasing mental HQOL scores (Chahal, Barker-Collo, & Feigin, 2011;Laffond et al, 2012).…”
Section: Health-related Qol and Cognitive Functionsmentioning
confidence: 99%
“…This shows the potential of exercise game as an intervention for promoting physical activity. It is known that compared to intense exercise, mild physical activities that do not exceed a subject's ability have no adverse effects and are more effective at depression 3,6,17) . The exercise game used as an intervention in the present study could be used as mild physical activities that do not impose physical or mental overload as they showed the possibility of relieving depression and improving the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is known to be the most important element in maintaining and improving the health of the elderly. Regular physical activity can increase independence in daily life, help relieve depression, and improve the quality of life of the elderly 3,4) . General exercises, such as muscle strengthening and endurance exercises, range of motion exercises, and stretching exercises, as well as functional and task-orientated exercise programs, are used to promote the physical activity of the elderly 5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…8 The effect of the programme on cognitive function was evaluated using the Digit Symbol Substitution Test (DSST) of the Wechsler Adult Intelligence Scale, 9 part A of the Trail-Making Test, 10 and Five Cognitive Tests. 11,12 The DSST assesses visual motor coordination, attention function, and processing speed. The part A of the Trail-Making Test assesses visual search speed, scanning, processing speed, mental flexibility, and executive functioning.…”
Section: Methodsmentioning
confidence: 99%